Pengembangan Media Pembelajaran Berbasis Audio Visual Untuk Meningkatkan Motivasi Belajar Siswa di SMP Muhammadiyah Waipare - Mia Ambarwati; Yuliana Dua Solo; Mariana Sada (Indo Publishing, 2026)
This research aims to determine the level of students' learning motivation by developing audio-visual-based learning media. Media is a means to convey messages or information that is intended to be communicated, and audio-visual learning media is one type of learning media used in teaching and learning activities. This audio-visual media has the capability to assist learning activities because it is applied using computer technology that can overcome limitations in students' experiences. Motivation and learning are two interrelated aspects and are a necessity for optimally developing students' abilities. Learning motivation has a strong influence on the success or the learning process of students. This research uses the R&D/Research and Development research method. Then, the data sources in this study were obtained from teachers, students, and expert lecturers, and the instruments used in this research were interviews, observations, and student learning motivation questionnaires.